Effectiveness and Safety of Apixaban for Treatment of Venous Thromboembolism in Daily Practice - Hendriks, Stephan V.; Klok, Frederikus A.; Stenger, Wilhelmina J.E.; Mairuhu, Albert T.A.; Eikenboom, Jeroen; Fogteloo, Jaap; Huisman, Menno V. (TH Open, 2020)
Introduction Phase 3 trials have shown comparable efficacy of direct oral anticoagulants (DOACs) and vitamin K antagonists in patients with acute venous thromboembolism (VTE), with less major bleeding events in patients randomized to DOAC treatment. With DOACs being increasingly used in clinical practice, evaluation of the DOACs in daily practice-based conditions is needed to confirm their safety and effectiveness. The aim of this study is to evaluate the effectiveness and safety of apixaban in VTE patients in daily practice.Methods In this retrospective cohort study, consecutive patients diagnosed with VTE in two Dutch hospitals (Leiden University Medical Center, Leiden and Haga Teaching Hospital, The Hague) were identified based on administrative codes. We assessed recurrent VTE, major bleeding and mortality during a 3-month follow-up period in those treated with apixaban.Results Of 671 consecutive VTE patients treated with apixaban, 371 presented with acute pulmonary embolism (PE) and 300 patients with deep-vein thrombosis. During 3 months treatment, 2 patients had a recurrent VTE (0.3%; 95% confidence interval [CI]: 0.08–1.1), 12 patients had major bleeding (1.8%; 95% CI: 1.0–3.2), and 11 patients died (1.6%; 95% CI: 0.9–2.9), of which one patient with recurrent PE and one because of a intracerebral bleeding.Conclusion In this daily practice-based cohort, apixaban yielded a low incidence of recurrent VTE, comparable to the phase 3 AMPLIFY study patients. The incidence of major bleeding was higher than in the AMPLIFY-study patients, reflecting the importance of daily practice evaluation and the fact that results from phase III clinical studies cannot be directly extrapolated toward daily practice.
Keywords: apixaban; direct oral anticoagulants; safety; efficacy; venous thromboembolism